Measuring Thinking Styles and Emotional Expressivity for HRM contexts: A test of two instruments in China - Feng, Y.; Ramalho, N. (29th EBES Conference - Lisbon, 2019)
Objectives: The east-west increasing business interchange is pushing human resource management to bridge people with contrasting cultures. More importantly, it must bridge different ways of thinking and expressing emotions, without which communication is ineffective. For this purpose, one has to be able to measure and manage thinking styles and emotional expressivity which has mostly been proposed by western scholars, not eastern ones. This research is intended to assess the quality of two dominant western-based measures on thinking styles and emotional expressivity with a Chinese sample to gauge the extent of its adequacy for comparative purposes. Data and methods: The second revised version of Sternberg’s Thinking Styles Inventory (TSI-R2,2007), and Berkeley Expressivity Questionnaire BEQ (Gross & John, 1995) were selected to measure thinking styles and emotional expressivity, respectively. With a two-phased full sample of 448 valid questionnaires, collected online both with Qualtrics and another Chinese survey platform - WJX, the construct validity was analyzed with Confirmatory Factor Analysis using SPSS AMOS 24. Results: With the first sample of 254, TSI-R2 and BEQ’s scale fit was tested. A valid solution was found only for a 7-factor structure suggesting TSI-R2 is overly complex, and may not be suited for Chinese research in HRM as is. BEQ failed to achieve acceptable fit indices for any solution, although the Joreskog’s Composite Reliability for the whole scale was above 0.8. By using the second sample of 448, the CFA fit indices for BEQ was suboptimal but still acceptable, so BEQ has plausible conditions to be used in China as is. Conclusions: The psychometric validation findings about TSI-R2 and BEQ provides insight on cross-cultural problems when targeting the measurement of cognitive and emotional processes, which underlie communication in multicultural organizational settings. Findings suggest constructs have to be simplified to reach a common ground and understanding on how to manage this fundamental difference within HRM.